Genetic diversity of Malaysian aromatic rice germplasm revealed by quantitative traits, microsatellite and intersimple sequence repeat markers - Al-Jumaily, Saba Jasim Mohamad (2015)
The study of genetic diversity among 50 aromatic rice accessions from Peninsular Malaysia, Sabah and Sarawak with 3 released varieties as a control was carried out through quantitative traits and molecular markers. The objectives of this research were (i) to evaluate the performance of different accessions of Malaysian aromatic rice, (ii) to determine the genetic diversity among the aromatic rice accessions, (iii) to quantify the genetic divergence of the aromatic rice accessions using microsatellite (SSR) and inter simple sequence repeat (ISSR) markers, and (iv) to identify superior accessions among the germplasm for future aromatic rice breeding program. Results from genetic diversity analysis based on 14 quantitative traits, showed that all the traits had significant variation among the accessions. The eight traits, namely plant height,1000-grain weight, yield per hill, number of panicles, spikelet fertility, number of grains per hill, flag leaf length to width ratio and panicle length indicated high level of broad sense heritability and genetic advance. These traits are regarded as important yield components for selection of superior rice genotypes. The broad sense heritability values for these traits were more than 91%, while genetic advance values of those traits ranged from 31.02 to 56.95%. Cluster analyses based on morphological traits grouped the 53 accessions into six clusters. The first four principal components based on the quantitative traits resulted into 71.3% of the total variation. Based on the quantitative analysis, Accessions Acc6288,average values for some traits namely, number of tillers per hill, 1000-grain weight,grain yield per hill, spikelet fertility and number of grains per hill. Genetic diversity analysis of the 53 rice accessions using 32 SSR and 25 ISSR polymorphic markers clustered the accessions into 10 groups and 8 groups respectively. Based on Analysis of molecular variance (AMOVA), SSR markers detected a high polymorphism within population (89%) and low polymorphism among populations (11%). ISSR markers also revealed similar trend with a high polymorphism within population (87%) and low polymorphism among populations (13%). Gene diversity (h) among the 53 accessions ranged from 0.045 to 0.976 using SSR markers, and while from ISSR markers, it ranged from 0.129 to 0.849. Several superior accessions have been identified for the future aromatic rice breeding program. These include Accession Acc6288 (Peninsular Malaysia), Acc9936 and Acc9971 (Sabah), and Acc11816 and Acc10538 (Sarawak). The selected accessions can be subjected to further evaluation and subsequent crossing program for aromatic rice varietal development. Acc9993, Acc11816, Acc9936, Acc9971 and Acc10538 indicated among the highest.